From Student to Teacher: Medical Student Perceptions of Teaching Children and a Novel Application of the One Minute Preceptor - Laura Cline; Muna Canales (International Journal of Medical Students, 2020)
Background: As students progress through medical school, the student assumes teaching roles, but without formal training regarding how to teach.